Mengajarkan Penginjilan sebagai Gaya Hidup Orang Percaya - Djuwansah Suhendro P. Stephanus (Sekolah Tinggi Teologia Kerusso Indonesia, 2019)
Evangelism must become the lifestyle of all believers. Evangelism agrees to preach the good news about salvation in Jesus Christ and win people to Him, according to the Great Commission in Matthew 28:19-20. We have to be a witness of Jesus Christ and His Gospel as our lifestyle. Being a Christian is like being a witness for Jesus. Evangelism and witnessing are a major part of a believer's life with values that are in accordance with Christ's teachings. The Lord Jesus became a positive example of how evangelism became His lifestyle. In practice, the church develops a discipleship process to help, direct and produce the results of the gospel message and establish new believers in fellowship, holy baptized, discipleship, and practice. Being externally applied in two important parts namely go and make all the tribes become disciples of Christ. These two external parts will be accomplished by an effective compilation that has been disciplined as a disciple of Christ holistically. This external implementation guides and encourages each church to diligently preach the Gospel of Christ as a lifestyle in various life discussions.